Biomechanical behaviour of human bile duct wall and impact of cadaveric preservation processes. (October 2019) - Girard, E.; Chagnon, G.; Gremen, E.; Calvez, M.; Masri, C.; Boutonnat, J.; Trilling, B.; Nottelet, B.
Abstract: Biliary diseases are the third most common cause of surgical digestive disease. There is a close relationship between the mechanical performance of the bile duct and its physiological function. Data of biomechanical properties of human main bile duct are scarce in literature. Furthermore, mechanical properties of soft tissues are affected by these preservation procedures. The aim of the present work was, on the one hand, to observe the microstructure of the human bile duct by means of histological analysis, on the other hand, to characterize the mechanical behavior and describe the impact of different preservation processes. A mechanical study in a controlled environment consisting of cyclic tests was made. The results of the mechanical tests are discussed and explained using the micro-structural observations. The results show an influence of the loading direction, which is representative of an anisotropic behavior. A strong hysteresis due to the viscoelastic properties of soft tissues was also observed. Embalming and freezing preservation methods had an impact on the biomechanical properties of human main bile duct, with fiber network deterioration. That may further provide a useful quantitative baseline for anatomical and surgical training using embalming and freezing. Highlights: Microstructure analysis allows explain mechanical behavior of bile duct wall. Bile duct is characterized by a strong hysteresis due to the viscoelasticity. Main bile duct wall is characterized by an anisotropic behavior. Preservation methods have an impact on the biomechanical properties. Embalming and freezing lead to fiber network deterioration.